2012
DOI: 10.1364/ao.51.001631
|View full text |Cite
|
Sign up to set email alerts
|

Generation of doubly charged vortex beam by concentrated loading of glass disks along their diameter

Abstract: We show that a system of glass disks compressed along their diameters enables one to induce a doubly charged vortex beam in the emergent light when the incident light is circularly polarized. Using such a disk system, one can control the efficiency of conversion of the spin angular momentum to the orbital angular momentum by a loading force. The consideration presented here can be extended for the case of crystalline materials with high optical damage thresholds in order to induce high-power vortex beams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…We have also found that superposition of the both electrooptic effects can result in the topological reactions of birth, adding and annihilation of the TDs [9][10][11]. According to our experimental data [12][13][14][15], the mechanical stresses of bending or torsion can also induce the TDs with the half-integer strength in many situations. In particular, the TDs of OI orientation with the strength module |1/2| appear in the amorphous glass media with residual stresses [16].…”
Section: Introductionmentioning
confidence: 67%
“…We have also found that superposition of the both electrooptic effects can result in the topological reactions of birth, adding and annihilation of the TDs [9][10][11]. According to our experimental data [12][13][14][15], the mechanical stresses of bending or torsion can also induce the TDs with the half-integer strength in many situations. In particular, the TDs of OI orientation with the strength module |1/2| appear in the amorphous glass media with residual stresses [16].…”
Section: Introductionmentioning
confidence: 67%
“…Recently we have shown that optical vortices can also be generated with the aid of parametric optical effects (e.g., piezooptic or Pockels ones) induced by inhomogeneous external fields [9][10][11][12]. For example, optical polarization singularities are successfully created using torsion of crystals, their bending [9][10][11], or loading of transparent crystalline disks compressed along their diameters [12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, optical polarization singularities are successfully created using torsion of crystals, their bending [9][10][11], or loading of transparent crystalline disks compressed along their diameters [12]. It has also been found that optical polarization singularities are imposed by structural dislocations existing in crystals or by residual stresses available in glass materials [13].…”
Section: Introductionmentioning
confidence: 99%
“…We remind in this respect that 2D distributions of external fields usually induce optical singularities, which appear when the incident nearly plane-wave optical beams propagate through crystalline samples (see [10][11][12][13][14][15]). The optical vortices can be induced by the mechanical stresses appearing under torsion [11,12] or bending [13,15] of crystalline samples, or under compression of disks made of optical material along their diameters [14].…”
Section: Introductionmentioning
confidence: 99%
“…The optical vortices can be induced by the mechanical stresses appearing under torsion [11,12] or bending [13,15] of crystalline samples, or under compression of disks made of optical material along their diameters [14]. Notice that all of the stressed states mentioned above correspond to 2D stress distributions.…”
Section: Introductionmentioning
confidence: 99%